THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON LIBRARY IMAGE - Ihsan, Muhammad; Prasastiningtyas, Widyapuri (TOPLAMA, 2025)
Research was conducted to determine the influence of Customer Relationship Management (CRM) on the image of libraries at the Bandung City Archives and Library Service. This research uses quantitative methods with descriptive research type, and the data analysis techniques used are descriptive analysis and multiple linear regression analysis. Based on the results of simultaneous hypothesis testing, Customer Relationship Management (CRM) has a significant effect on the image of the Bandung City Archives and Library Service. This is proven by Fcount > Ftable (30.343 > 2.440) with a significance level of 0.000 < 0.0005. Based on the results of partial hypothesis testing (t-test), it was found that data, technology, human resources, and process variables had a significant effect on the image of the Bandung City Archives and Library Service. Based on the coefficient of determination, it was found that Customer Relationship Management (CRM) was able to explain 47.7% of the library's image, while the remaining 52.3% was influenced by other factors that were not researched.